Sistem Pendukung Keputusan Pemilihan Negara Untuk Studi S1 di Asia Tenggara Berbasis Website dengan Menggunakan Metode Topsis - Nugrahani, Fitria; Hayati, Paramidita Nurul; Ismail, Iklima Ermis (MULTINETICS, 2018)
Southeast Asia is one part of the Asian country that has many leading universities, one of them in Indonesia. Therefore, many students wish to continue their undergraduate studies in Southeast Asia. However, students sometimes feel confused choosing a destination country for undergraduate study in Southeast Asia. Based on these problems, the authors make Decision Support System of State Election for Study S1 in Southeast Asia to assist students in choosing a country for study S1. The author makes this decision support system using 5 States as an alternative.This System using TOPSIS Method to calculate and determine which countries that would be the best recommendation for studies. This method could be effective for the recommendation.